Dr. IOT – Automated HealthCare System - Arnab Hazra,S Shashank,Shubhrajyoti Das (International Journal of Advanced Science and Technology, 2020)
In today’s busy life along with the rise of diseases, there is hardly any time to consider our health issues. This Arduino-based project tackles this issue by helping us in health care in various ways. It works as an automatic medicine reminder, which informs the patient of the dosage as well as the timing. It mainly focuses on patients suffering from neurological conditions. In case of emergencies, it provides the facility of notifying the listed contacts and the nearest hospital. Also, it can check the body temperature, pulse rate, and many more biological parameters. There have been many such projects in the past, but we aim to create a cost efficient version.